Training of nurses in primary health of women - Márcia Sousa Santos; Maria Eliete Batista Moura; Inez Sampaio Nery; Eliana Campêlo Lago; Benevina Maria Vilar Teixeira Nunes (Revista de Pesquisa Cuidado é Fundamental Online)
Objectives: To evaluate the influence of the nursing education process in primary care related to women's health. In addition, to analyze nursing training in primary care for women's health and as a National Policy for Comprehensive Care of Women's Health. Method: An exploratory study with 30 nurses from the Family Health Strategy. Data were generated through interviews, processed and analyzed in Alceste4.8 by Descending Hierarchical Classification. Results: The data were presented as dendrogram classes: training at the graduate level to work in the area of women's health; the work of nurses in primary care to women's health; the Program for Integral Attention to Women's Health in primary care and continuing education of nurses in primary health care of women. Final considerations: Permanent education of nurses is necessary for the promotion healthcare and public policy on care for women.